2021
DOI: 10.1186/s13756-021-00940-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of antibiotic prescriptions: a knowledge, attitude and practice survey among physicians in tertiary hospitals in Nigeria

Abstract: Background As part of the Global Action Plan against antimicrobial resistance (AMR), countries are required to generate local evidence to inform context-specific implementation of national action plans against AMR (NAPAR). We aimed to evaluate the knowledge, attitude, and practice (KAP) regarding antibiotic prescriptions (APR) and AMR among physicians in tertiary hospitals in Nigeria, and to determine predictors of KAP of APR and AMR. Methods In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
8
17
0
1
Order By: Relevance
“…Increased awareness on AMR among healthcare students has been shown to be an effective approach to improving future practitioners’ prescribing behavior [ 47 ]. This is important as there have been concerns with knowledge regarding antibiotics and AMR among healthcare professionals in Africa and the implications thereof [ 41 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased awareness on AMR among healthcare students has been shown to be an effective approach to improving future practitioners’ prescribing behavior [ 47 ]. This is important as there have been concerns with knowledge regarding antibiotics and AMR among healthcare professionals in Africa and the implications thereof [ 41 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge, attitude, and practice (KAP) studies are targeted at discovering and understanding a peculiar population's knowledge and approach towards a particular topic of interest hence conducting such studies bring to the fore existing knowledge gaps. Some KAP studies on AMR have been conducted among relevant stakeholders in Nigeria which identified gaps in AMS awareness [ 17 21 ]. Studies carried out among Nigerian veterinary students reported that 60% had an unsatisfactory level of knowledge of AMR while only about 7% knew the meaning of antimicrobial stewardship [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A sample size of 245 was calculated to be the minimum required, assuming that 20% of primary care physicians have good practices ( 13 ), and a 95% confidence interval (CI), with 0.05 absolute precisions on either side of the predicted proportion. We inflated the number to 336 to account for an expected non-response rate of 40% among participants ( 14 ).…”
Section: Methodsmentioning
confidence: 99%